Autophagy facilitates the release of immunogenic signals following chemotherapy in 3D models of mesothelioma. Issue 10 (19th June 2019) - Follo, Carlo; Cheng, Yao; Richards, William G.; Bueno, Raphael; Broaddus, V. Courtney
Abstract : We have previously shown that nearly half of mesothelioma patients have tumors with low autophagy and that these patients have a significantly worse outcome than those with high autophagy. We hypothesized that autophagy may be beneficial by facilitating immunogenic cell death (ICD) of tumor cells following chemotherapy. An important hallmark of ICD is that death of tumor cells is preceded or accompanied by the release of damage‐associated molecular pattern molecules (DAMPs), which then can stimulate an antitumor immune response. Therefore, we measured how autophagy affected the release of three major DAMPs: high mobility group box 1 (HMGB1), ATP, and calreticulin following chemotherapy. We found that autophagy in three‐dimensional (3D) models with low autophagy at baseline could be upregulated with the cell‐permeant Tat‐BECN1 peptide and confirmed that autophagy in 3D models with high autophagy at baseline could be inhibited with MRT 68921 or ATG7 RNAi, as we have previously shown. In in vitro 3D spheroids, we found that, when autophagy was high or upregulated, DAMPs were released following chemotherapy; however, when autophagy was low or inhibited, DAMPs release was significantly impaired. Similarly, in ex vivo tumors, when autophagy was high or upregulated, HMGB1 was released following chemotherapy but, when autophagy was low, HMGB1 release was not seen. We conclude that autophagy can be upregulated in at least some tumors with low autophagy and that upregulation of autophagy can restore the release of DAMPs following chemotherapy. Autophagy may be necessary for ICD in this tumor.